Depression, anxiety and stress among patients receiving methadone maintenance therapy and its associated factors; a cross sectional study in primary care clinics, Malaysia - Md Aris, Mohd Aznan; Said, Abdul Hadi; Tin, Myo Han; Abdullah, Fa’iza; Mohd Sahar, Nurakmal; Abdul Hamid, Muhammad Firdaus; Mohd Khanafiah, Muhammad Farisham; Mohamad Fauzi, Muhammad Syahir; Mohamad, Ramzi Akram (The International Journal of Education and Psychological Research (IJEPR), 2018)
Objectives: Several studies have reported the high prevalence of psychiatric problems in patients receiving Methadone Maintenance Therapy. This study measured the prevalence of depression, anxiety and stress among patients receiving Methadone Maintenance Therapy in Malaysia and its predictors.